Hubungan Kualitas Tidur Dengan Tekanan Darah Pada Pasien Stroke Di Rumah Sakit Mitra Medika Tanjung Mulia Medan - Putri Purnama Sari; Maya Ardilla Siregar; Hizrah Hanim Lubis (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2025)
Introduction: Stroke is a neurological disorder characterized by blockage of blood vessels. Clots that form in the brain and interfere with blood flow, clog arteries and cause blood vessels to rupture, causing bleeding. The rupture of an artery leading to the brain due to a stroke results in the sudden death of brain cells due to lack of oxygen. Objective: The purpose of this study was to determine the relationship of sleep quality with blood pressure in stroke patients at Mitra Medika Tanjung Mulia Hospital Medan. Methods: The research design used in this study using analytical survey method with crosses sectional approach. The population in this study was all stroke patients who were in outpatient facilities at Mitra Medika Tanjung Mulia Hospital Medan, which amounted to 90 respondents. Sampling used is by means of purposivesampling sampling techniques by determining certain criteria. Results: Based on the results of analysis using The Chi-Square test showed a significant value of probability bawha (Asymmp.Sig) sleep quality is 0.033 or < SIG a value = 0.05. This proves that there is a relationship between sleep quality and blood pressure in stroke patients at Mitra Medika Tanjung Mulia Hospital Medan. Conclusion: there is a relationship of sleep quality with blood pressure in stroke patients at Mitra Medika Tanjung Mulia Hospital Medan in 2025.